Immediate online use of prosody reveals the ironic intentions of a speaker: neurophysiological evidence. - Mauchand, Maël; Caballero, Jonathan A.; Jiang, Xiaoming; Pell, Marc D. (Cognitive, Affective & Behavioral Neuroscience, 2021)
In social interactions, speakers often use their tone of voice ("prosody") to communicate their interpersonal stance to pragmatically mark an ironic intention (e.g., sarcasm). The neurocognitive effects of prosody as listeners process ironic statements in real time are still poorly understood. In this study, 30 participants judged the friendliness of literal and ironic criticisms and compliments in the absence of context while their electrical brain activity was recorded. Event-related potentials reflecting the uptake of prosodic information were tracked at two time points in the utterance. Prosody robustly modulated P200 and late positivity amplitudes from utterance onset. These early neural responses registered both the speaker's stance (positive/negative) and their intention (literal/ironic). At a later timepoint (You are such a great/horrible cook), P200, N400, and P600 amplitudes were all greater when the critical word valence was congruent with the speaker's vocal stance, suggesting that irony was contextually facilitated by early effects from prosody. Our results exemplify that rapid uptake of salient prosodic features allows listeners to make online predictions about the speaker's ironic intent. This process can constrain their representation of an utterance to uncover nonliteral meanings without violating contextual expectations held about the speaker, as described by parallel-constraint satisfaction models.